Abnormal Connectivity Within Executive Resting‐State Network in Migraine With Aura. Issue 6 (June 2015) - Tessitore, Alessandro; Russo, Antonio; Conte, Francesca; Giordano, Alfonso; De Stefano, Manuela; Lavorgna, Luigi; Corbo, Daniele; Caiazzo, Giuseppina; Esposito, Fabrizio; Tedeschi, Gioacchino
<x xml:space="preserve">Abstract</x> Objective To evaluate the executive control network connectivity integrity in patients with migraine with aura, in the interictal period, in comparison to patients with migraine without aura and healthy controls. Methods Using resting‐state functional magnetic resonance imaging, we compared executive control network functional connectivity in 20 patients with migraine with aura vs 20 sex and age‐matched patients with migraine without aura and 20 healthy controls, and assessed the correlation between executive control network functional connectivity and clinical features of patients with migraine. We used voxel‐based morphometry and diffusion tensor imaging to investigate potential structural or microstructural changes. Results Neuropsychological data revealed no significant executive dysfunction in patients with migraine. Resting‐state functional magnetic resonance imaging showed significant group differences in right middle frontal gyrus (Talairach coordinates x, y, z: +26, +2, +48) and dorsal anterior cingulate cortex (Talairach coordinates x, y, z: +6, +13, +49), indicating that these areas had a decreased component activity in both patients with migraine with and without aura when compared with healthy controls. Conversely, there were no significant differences in the executive control network functional connectivity between patients with migraine with and without aura (P < .05, cluster‐level corrected). These functional abnormalities are independent of structural and microstructural changes and did not significantly correlate with clinical parameters. Conclusions Our data demonstrate a disrupted executive control network functional connectivity in patients with migraine with and without aura, in the interictal period. Although this functional phenomenon is present in the absence of clinically relevant executive deficits, it may reflect a vulnerability to executive high‐demanding conditions of daily living activities in patients with migraine.